Gambaran Pola Penggunaan Antipsikotik Pada Pasien Skizofrenia Di Ruang Rawat Inap Rumah Sakit Jiwa Provinsi Jawa Barat - Entris Sutrisno; Yani Mulyani; Jajang Japar Sodik (Pengurus Pusat Ikatan Apoteker Indonesia, 2026)
Indonesia experiences an alarming increase in mental disorder cases annually. In 2019, the World Health Organization reported that over 20 million individuals worldwide suffer from schizophrenia. Antipsychotic medications are the preferred treatment option for schizophrenia, as they help alleviate psychotic symptoms and reduce the likelihood of developing the disorder. This study aimed to describe the use of antipsychotic drugs in patients with schizophrenia in the inpatient ward of the Mental Hospital of West Java Province. The study employed a non-experimental, descriptive design with retrospective data collection. Secondary data were used for analysis. The research focused on 194 medical records of patients who received antipsychotic treatment between January and December 2020. The study revealed that 56.19% of prescribed antipsychotic drugs were combination medications, while 43.81% were single drugs. The most common combination of antipsychotic drugs was haloperidol-clozapine, accounting for 36.60% of the prescriptions, and risperidone, a single drug, comprised 19.67% of the prescriptions.